FAKTOR LINGKUNGAN DAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DAERAH ENDEMIS KECAMATAN GADING CEMPAKA KOTA BENGKULU - Helfi Nolia; Erba Kalto (Poltekkes Kemenkes Medan, 2022)
Incidence Rate (IR) of Dengue Hemorrhagic Fever (DHF) in Bengkulu Province in 2011 was reported 129.76 per 100,000 population and Case Fatality Rate (CFR) was reported 1.73%. Data obtained from Bengkulu City Health Services, was showed that DHF cases was increased since 2008, and in 2011 was reported of 403 cases. The incidence of DHF cases in Gading Cempaka Sub District was 139 in 2011. Epidemiological studies was conducted to determine the risk factors associated with DHF incidence, Ae.aegypti mosquito resistance to malathion and temephos and distance index of the distribution was conducted in Sub District Gading Cempaka, Bengkulu city in 2011. The study was conducted in an effort to decide an appropriate vector control method to be applied in the study area. There for determine risk factors of DHF transmission such as dwelling density, indoor illumination , larvae free index (LFI), regular household sanitation or clean-up campaigns (to dry of, cover and bury/the vector habitats cleaning), and cloth hanging habit the incidence of DHF, the Ae. aegypti mosquito resistance to malathion and temefos and distance index of DHF cases.